College of Library Science and Archives teacher's emotions at UNAM during COVID-19 lockdown - Guevara Villanueva, Angélica (2023)
The article shows part of the results of a survey applied to 115 teachers at the end of 2021 and the beginning of 2022 assigned to the College of Library Science and Archives of the Faculty of Philosophy and Letters of the National Autonomous University of Mexico. The objective was to know the emotions involved in the online teaching process during and at the end of lockdown based on four thematic axes: physical space; technological equipment and Internet connection; interaction with students and post-pandemic. The results reflect a higher frequency of positive emotions rather than negative related to the physical space, with the technological equipment and Internet connection in teachers, which allows inferring a favorable emotional state. Likewise, the teachers expressed empathy and solidarity towards the problems that affect the interaction with their students. However, despite the fact that there is a positive emotion for the return to face-to-face classes, even in a hybrid modality, the teachers reaffirmed the importance of having specialized support in managing emotions.